Efficacy and Safety of Exercise Training in Chronic Pulmonary Hypertension: Systematic Review and Meta-Analysis. (November 2015) - Pandey, Ambarish; Garg, Sushil; Khunger, Monica; Garg, Sonia; Kumbhani, Dharam J.; Chin, Kelly M.; Berry, Jarett D.
Abstract : Background—: Exercise training has been shown to improve cardiorespiratory fitness, physical capacity, and quality of life in patients with cardiopulmonary conditions, such as heart failure and chronic obstructive pulmonary disease. However, its role in management of pulmonary hypertension is not well defined. In this study, we aim to evaluate the efficacy and safety of exercise training in patients with pulmonary hypertension. Methods and Results—: We included all prospective intervention studies that evaluated the efficacy and safety of exercise training in patients with pulmonary hypertension. Primary outcome of this meta-analysis was a change in 6-minute walk distance. We also assessed the effect of exercise on peak oxygen uptake, resting pulmonary arterial systolic pressure, peak exercise heart rate, and quality of life. A total of 469 exercise-training participants enrolled in 16 separate training studies were included. In the pooled analysis, exercise training was associated with significant improvement in 6-minute walk distance (weighted mean difference, 53.3 m; 95% confidence interval, 39.5–67.2), peak oxygen uptake (weighted mean difference, 1.8 mL/kg per minute; 95% confidence interval, 1.4–2.3), pulmonary arterial systolic pressure (weighted mean difference, −3.7 mm Hg; 95% confidence interval, −5.4 to −1.9), peak exercise heart rate (weighted mean difference, 10 beats per min; 95% confidence interval, 6–15), and quality of life as measured on SF-36 questionnaire subscale scores. Furthermore, exercise training was well tolerated with a low dropout rate, and no major adverse events were related to exercise training. Conclusions—: Exercise training in patients with pulmonary hypertension appears safe and is associated with a significant improvement in exercise capacity, pulmonary arterial pressure, and quality of life. Abstract : Supplemental Digital Content is available in the text.